INTRAVITREL BEVACIZUMAB IN DIFFERENT TYPE OF RETINAL VEIN OCCLUSIONS - Laghari, Dilshad; Rehman, Aziz Ur; Qidwai, Umair; Talpur, Abdul Hameed (Journal of Ayub Medical College Abbottabad, 2015)
Background: Retinal vein occlusion is frequent cause of visual loss with insufficient treatment options. Many treatment options have been tried in the past including intravitreal triamcenoloneacetonide injection. This study was conducted to evaluate the efficacy and complications of intravitreal injection of Bevacizumab in different types of retinal vein occlusion. Methods: This interventional study was carried out at Al Ibrahim eye hospital, Karachi from July 2011 to December 2012. Patients diagnosed with retinal vein occlusion of any type were included in the study using non-probability purposive sampling technique, after informed written consent. Patients were injected intra-vitreally with Bevacizumab 1.25 mg/0.05 ml under sterilized technique in operation room. Best corrected visual acuity and optical coherence tomography was repeated in every follow up along with the detailed fundoscopy and intraocular pressure measurement. Data analysis was done using SPSS-20.0. Results: A total 278 patients were included in the study according to the inclusion and exclusion criteria. Mean age of the patients was 54.28 years (SD=5.62). Out of 278 patients included in the study, 132 had BRVO, 141 had CRVO while 5 had HRVO. Mean visual acuity before injection was 2.309 lines of Snellen's acuity chart read, with minimum of 1 line read and maximum of 4 lines read (standard deviation=1.00). After 12 weeks post injection, 92 patients read 7 lines (6/6) of Snellen's visual acuity chart. Mean visual acuity was 4.75 lines of Snellen's acuity chart read, with minimum of 1 line read and maximum of 7 lines read (standard deviation=1.00). 77% of the patients had visual improvement after injection (p<0.05). Conclusion: Intravitreal bevacizumab injection is very effective in reducing macular thickness as well in improving visual acuity in all types of retinal vein occlusion.